Model of evaluation of enterprise risk management - Mackevičius, Jonas; Giriūnas, Lukas (Buhalterinės apskaitos teorija ir praktika, 2014)
It should be noted that in this article the enterprise‘s activity risk management and evaluation problem is defined. The risk classification is defined in these criteries: coming way, effect, activity‘s area, time, probability of result, probability of management, importance and misuses. The model of evaluation of enterprise risk management is recommended. The model consists of these stages of risk management and evaluation: 1) identification of enterprise activity internals, 2) identification of risk determinants, 3) risk identification, 4) evaluation of risk level, 5) evaluation of risk consequence, 6) system of risk management tools, 7) evaluation of costs of risk management, 8) choice of strategy of risk management, 9) evaluation of results.